Recursos educativos digitales utilizados por los docentes para el proceso de enseñanza del subnivel básica media en las cuatro áreas de conocimiento de la escuela de Educación Básica Zoila Alvarado de Jaramillo, en el año lectivo 2022-2023. - Pintado Jumbo, Melania Marisol (2023)
Digital educational resources are used as a didactic medium for the teaching and learning process. Therefore, the main objective of this research is to describe the digital educational resources used by teachers in the teaching process of the middle basic level in the four areas of knowledge: Mathematics, Natural Sciences, Social Sciences, Language, and Literature. This study was conducted at Zoila Alvarado de Jaramillo Basic Education School. As for the methodology, the deductive study method was used along with a descriptive quantitative approach. The population consisted of 28 teachers, and the techniques and instruments used in this study were based on a structured questionnaire called "Digital Educational Resources in the Teaching Process," which was administered through the survey technique. The results mention various digital educational resources classified by communication, virtual content, authorship, platforms or learning environments, collaboration, social networks, notes, and transfer. Among the most commonly used resources are Word, PowerPoint, Excel, WhatsApp, emails, websites, and the social network Facebook, while the least used ones are Publisher, OneNote, Voice Messages IP, and Blackboard. These resources were analyzed and classified in a table that describes them according to parameters such as area of knowledge, middle basic level, classification, characteristic, type, and description. In this way, digital educational resources that support the teaching process in the four areas of knowledge were identified. Finally, it is suggested that the authorities and educational stakeholders of the participating institution manage training regarding the use of digital educational resources and their implementation in the classroom. Keywords: Digital educational resources, Teaching process, Areas of knowledge, basic education..